Nanomaterial Adjuvants for Veterinary Vaccines: Mechanisms and Applications - Li He; Ruliang Pan; Rui Liang; Bingyao Li; Pei Zhang; Shujun He; Baoguo Li; Yuli Li (Research)
Safe and effective veterinary vaccines prevent infectious diseases and reduce morbidity. In this field, nanovaccines based on nanomaterials are emerging, showing great potential as innovative alternatives to conventional vaccines. This paper highlights the advantages, disadvantages, and mechanisms of nanomaterials, including biomimetic, polymeric, lipid nanoparticles, self-assembling proteins, and other materials used in veterinary vaccine development. We also describe the progress of their research in developing vaccines against common and serious veterinary infectious diseases, such as foot-and-mouth illness, porcine epidemic diarrhea, pseudorabies, and bordetellosis. We aim to provide a scientific basis and practical guidance for the research and development of new veterinary vaccines, thereby contributing to scientific and technological progress in the field of veterinary medicine and the protection of animal health.